2021
DOI: 10.1111/cea.13979
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing fruit and vegetable intake in children with asthma: A randomized controlled trial

Abstract: Background A high fruit and vegetable (F&V) diet reduces asthma exacerbations in adults; this has not been examined in children to date. Objective To investigate the effect of a 6‐month, high F&V diet on the time to first asthma exacerbation in children with asthma, in a parallel‐group, randomized, controlled trial. Methods Children (aged 3–11 years) with asthma, history of exacerbations and usual low F&V intake (≤3 serves/day) were randomized to the intervention (high F&V diet) or control group (usual diet) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The complete study design and methodology have been described previously [ 26 ]. Participants were recruited via attendance to the emergency department or admission to the John Hunter Children’s Hospital, Newcastle, Australia, and Maitland Hospital, Newcastle, Australia, following an asthma exacerbation, from September 2015 to July 2018.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete study design and methodology have been described previously [ 26 ]. Participants were recruited via attendance to the emergency department or admission to the John Hunter Children’s Hospital, Newcastle, Australia, and Maitland Hospital, Newcastle, Australia, following an asthma exacerbation, from September 2015 to July 2018.…”
Section: Methodsmentioning
confidence: 99%
“…This study reports secondary findings from an RCT that delivered a 6-month dietary intervention to increase F&V intake in children with asthma [ 26 ]. We have previously demonstrated that high F&V diet for 6 months did not prevent exacerbations, though it was associated with improvements in lung function [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other approaches to infant skincare do not seem to impact allergic disease development 5 . We also know that there is no causal association between serum vitamin D levels and risk of rhinitis or allergic sensitization, at least in a European‐ancestry population 6 and that while dietary antioxidants may promote improved lung function and respiratory health, 7 the first randomized controlled trial of increasing fruit and vegetable intake in asthmatic children did not impact asthma exacerbations over a 6‐month period 8 . In this issue of the journal, we publish several articles which make important contributions to our understanding of the early‐life origins of allergic conditions.…”
Section: Figurementioning
confidence: 99%
“…From this perspective, pure fruit juice may be more comparable with whole fruit in its association with asthma. Available evidence is weak but supportive for the hypothesis that fruit consumption is associated with lower prevalence of asthma and asthma symptoms ( Berthon et al, 2021 , Hosseini et al, 2017 , Garcia-Larsen et al, 2016 , Nurmatov et al, 2011 ). Pure fruit juice can be both fresh juice and bottled juice from concentrate and never contains added sugars, artificial sweeteners or components as artificial colors and preservatives.…”
Section: Introductionmentioning
confidence: 99%